Contribuição ao estudo das propriedades mecânicas do concreto autoadensável e do concreto autoadensável reforçado com fibras de aço - Paulo de Castro Guetti (2012)
The main objective of this work is the experimental analysis of the mechanical behavior of self-compacting concrete (SCC) and steel fiber reinforced self-compacting concrete (SFRSCC). For this, we considered the influence of the following variables on the mechanical behavior of the CAA: the maximum diameter of the aggregate, the particle size distribution and compressive strength. In the SFRSCC case, further to the three variables mentioned above we also considered the influence of the amount of steel fibers and the aspect ratio of the fibers. In order to obtain the fracture energy of SCC and the residual strength of SFRSCC, several three point bending tests using beams with a notch at the middle span were performed. Four concrete mixtures were designed to produce the SCC and eight mixtures for the SFRSCC as well. Further, four and eight mixtures to obtain respectively conventional vibrated concretes (CVC) and steel fiber reinforced conventional vibrated concretes (SFRCVC) were designed. The vibrated concretes have been adopted as a reference in order to perform comparisons of the results. The tests for characterization of the mechanical concrete behavior, based on fracture mechanics of quasi-brittle materials, have been carried out according to the following RILEM specifications: 50-FMC, TC 89-FMT, TC 89-FMT, which takes into account the size effect, and the specification TC 162-TDF for steel fiber reinforced concretes. The experimental results of these tests are represented by load versus CMOD (crack mouth opening displacement) curves. The compressive and tensile tests and the test to obtain the Youngs modulus of the concretes have been carried out on cylindrical specimens (15 cm x 30 cm). Additional tests on cubic specimens (with 10 cm edges) to determine the compressive of the concretes were also performed. In addition to the tests mentioned above, we used a method of digital image correlation and the technique of acoustic emission in order to evaluate the fracture energy and the size of the fracture process zone. The results from the digital image correlation were fully consistent with those obtained by means of other methods used in this research. The digital image correlation has been proved to be a low cost methodology, efficient and accurate, fully applicable not only to the types of testing adopted in this work, but also to several other experimental tests usualy applied in the lab environment during the characterization of structural materials